2006
DOI: 10.1364/josaa.23.002613
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive wavefront control with asynchronous stochastic parallel gradient descent clusters

Abstract: A scalable adaptive optics (AO) control system architecture composed of asynchronous control clusters based on the stochastic parallel gradient descent (SPGD) optimization technique is discussed. It is shown that subdivision of the control channels into asynchronous SPGD clusters improves the AO system performance by better utilizing individual and/or group characteristics of adaptive system components. Results of numerical simulations are presented for two different adaptive receiver systems based on asynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 17 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…As final remark, taking into account that the turbulence imposes a constraint to this modulation scheme, the use of adaptive algorithms can mitigate the turbulence‐induced wavefront distortion effect …”
Section: Resultsmentioning
confidence: 99%
“…As final remark, taking into account that the turbulence imposes a constraint to this modulation scheme, the use of adaptive algorithms can mitigate the turbulence‐induced wavefront distortion effect …”
Section: Resultsmentioning
confidence: 99%
“…Though in experiments the refractive index is not a direct measurable parameter, one can always use temperature and pressure sensors to extract relative refractive index deviations, which serves as a practical way for finding inputs for a simulative estimation of the channel. For a Gaussian beam, similar methods have been applied and Fig 8-11 are turbulence effects on coherent beam, partial coherent beam (like diode laser signal), random walk fitting and equivalent C n 2 according to equation (14). Though the simulation ignores the small eddies refraction behaviors, it gives a good estimation of the turbulence level and its distortion on the beam.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Based on the theoretical results of equation (14) and equation (15), both would converge to the same dominant z 3 term in linear portion to C n 2 if the propagation distance is long enough. With the help of deformable mirrors, one can intentionally pre-distort the beam a little by adding regional tilts through guidance from initial beam distortion, and the resultant "random walk" would be reduced and lead to an equivalently smaller C n 2 .…”
Section: Possible Correctionsmentioning
confidence: 99%
“…D-SPGD algorithm incorporates features of both wave-front sensor-based adaptive optics and model-free gradient descent optimization wave-front control, which offers fast adaptation convergence even for high-resolution adaptive optics. In [24] it is shown that subdivision of the control channels into asynchronous SPGD clusters improves the AO system performance by better utilizing individual and/or group characteristics of adaptive system components. Following the idea of defining vector cost function proposed in [18] and [25], in the present section, we propose cross-grouped SPGD algorithm, in which cost function information is transferred unidirectional, and also a few more detectors are required.…”
Section: Bandwidth Improvement Methods and Analysismentioning
confidence: 99%